Critical mass and substantive representation : a study of the legislative effectiveness of nominated female members of county assemblies in Kenya - Sidha, Zedekia Opondo (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.